Entanglement analysis of isotropic spin-1 chains. (16th July 2015) - Thomale, Ronny; Rachel, Stephan; Bernevig, B Andrei; Arovas, Daniel P
Abstract: We investigate entanglement spectra of the SO(3) bilinear-biquadratic spin-1 chain, a model with phases exhibiting spontaneous symmetry breaking (both translation and spin rotation), points of enlarged symmetry, and a symmetry-protected topological phase (the Haldane phase). Our analysis reveals how these hallmark features are manifested in the entanglement spectra, and highlights the versatility of entanglement spectra as a tool to study one-dimensional quantum systems via small finite size realizations.